Análisis del control de caudal en el proceso de separación de producción de petróleo, en el campo petrolero en la provincia Francisco de Orellana en el año 2016. construcción de un banco de pruebas de un sistema de control de caudal para evaluar la eficiencia en los procesos de separación. - Pacheco Mena, Carlos Francisco (2017)
A research study on the analysis of a flow control system in an oil separation plant was carried out through the implementation of a test system that was evaluated the energy efficiency. For this research project, control devices with industrial characteristics were used. These were similar to those used in oil separation. The fluid used was water. The initial factors such as Kc, Ti and Td of tuning of the controller for the flow control loop were identified through some instability tests according to Ziegler-Nichols’ Open-Loop and Closed-Loop Methods. These factors should be considered as initial data of the control system, which usually require a subsequent fine tuning through several disturbance tests of the system that will allow correcting the tuning factors of control to find the desired behavior and performance. During the tests of variation of the system variable, it was observed that the value of the current in the pump motor has variations according to the opening of the flow control valve. It means that if there is an oscillation of the variable, there is also variation in the energy consumption of the pump in order of 6,7 %. It determines that the highest efficiency in the system is when the process variable is in stable form and the flow control loop is fully tuned.